PENGARUH METODE PICTURE AND PICTURE DALAM MINAT BELAJAR MENULIS TEKS PUISI PADA SISWA SMA - Lovita Wulandari; Sirli Novia Mayaningrum; Riana Dwi Lestari (IKIP Siliwangi, 2019)
This research is motivated by the curiosity of researchers regarding the effect of using the picture and picture method in writing poetry texts in class XI students. This research was conducted to determine the level of success obtained in the use of the picture and picture method in writing poetry texts. The first activity carried out when the study was observed when the learning process was running, then a questionnaire was given to students. The selected subjects were class XI Language students totaling 22 people. The formulation of the problem contained, 1) is the picture and picture method effectively applied in learning to write poetry texts? 2) can the picture and picture learning method increase students' interest in learning text writing poetry? There are also research objectives, among others, 1) to determine the effectiveness of learning to write poetry texts using the method of picture and picture 2) to increase students' interest in learning to write poetry texts using the picture and picture method. The method applied in this study is descriptive qualitative. The researcher chose the technique of collecting data by observing and testing. The results of the study show that the picture and picture method is suitable for writing poetry texts. This can be seen with an increase in the value of 10.8% from the average value of 79.7 pretests and posttest average value 88.3.